The role of arthroscopy in the treatment of common wrist disorders: A retrospective clinical study (Annals of Medical Research, 2021)
Aim: The purpose of this research was to evaluate clinical and functional results of patients that we treated them with wrist arthroscopy.Material and Methods: Patients treated with wrist arthroscopy between February 2012 and June 2017 were retrospectively evaluated. Patients’ disease, treatment, effected side, preoperative and postoperative Quick Disabilities of the Arm, Shoulder and Hand (Q-DASH) score and postoperative Mayo score were recorded.Results: There were 78 (49 female and 29 male) patients. Mean age was 38±14.91 (16-81 years) years. Mean follow-up time was 45,4±17.93 (range, 6-72 months) months. There were 22 (28.2%) ganglion cyst, 15 (19.2%) triangular fibrocartilage complex tears, 11 (14.1%) Kienböck’s disease and 8 (10.3%) intraarticular distal radius fracture. All patients Quick-DASH scores statistically significantly improved at final follow-up compared to preoperative status (p
Keywords: Ganglion cyst; Kienböck's disease; TFCC tear; Wrist arthroscopy